Master-Slave Synchronization of Robotic Arm using PID Controller - Yin Hnin Thet Htun; May Su Hlaing; Tin Tin Hla (IAES Indonesian Section, 2023)
This paper analyzes the position control of a master-slave synchronization robotic arm driven by a D.C. motor using a PID (Proportional, Integral, and Derivative) controller with software and hardware design. This controller works to achieve the exact desired position simultaneously for the master and slave robot arm with minimal defects. The transfer function of the D.C. motor for the robotic arms used in this research is calculated with black box modelling. MATLAB Simulink block is used to test the software result. The MATLAB built-in auto-tuning method obtains Kp, Ki and Kd gain. These gains are adjusted with manual tuning to get precise angular positions for two robotic arms. This research uses Arduino Uno to act as a controller in the experiment. First, the position control of one robotic arm is tested with the same PID gain in MATLAB Simulink at different input degrees. Then, the hardware experiment of position control in one robotic arm is operated with only one PID gain at various reference degrees. Finally, the I2C communication protocol connects the master and slave robot arms. The main work that the PID controller hardware experiment with controls different level angular positions of two robotic arms.